Computational analysis of the rotating cylinder embedment onto flat plate - Mohammad Ali, Hidayatullah; Mohd Rafie, Azmin Shakrine; Md Ali, Syaril Azrad; Gires, Ezanee (Penerbit Akademia Baru, 2021)
The Magnus effect and its evolution have greatly affected the aerospace industry over the past century to date. Nevertheless, cylinder embedment onto a flat plate offers a new discovery that is yet to be investigated, specifically whether the concept could enhance the aerodynamic properties of the flat plate following the Magnus effect momentum injection. Over the past decade, the use of a rotating cylinder on an aerofoil has existed from past researches studies where the embedment has significantly increased in its aerodynamic performance better than the one without Magnus application. However, it would be hard to achieve experimental-wise as an accurate measurement and fabrication would be needed to have the same resulting effects. Here, most of the researchers would not focus deeply on the placement of the cylinder as this may increase their fabrication and testing complications. Therefore, the current study delineates the use of flat plate as the foundation design to encounter the arise matter by reducing its complication yet easy to manufacture experimentally. In this work, the model output was evaluated by using ANSYS WORKBENCH 2019 software to simulate two-dimensional flow analysis for the rotational velocities of 500 RPM and 1000 RPM, respectively. This was done for different Reynolds numbers ranging from 4.56E+05 to 2.74E+06 which implicitly implied with free stream velocities varying from 5 m/s to 30 m/s for different angles of attack between 0 to 20 degrees. Prior to developing the best model embedment, the mesh independency test was validated with an error of less than 1%. The study resulted in a remarkable trend that was noticeably up to 32% (500 RPM) and 76% (1000 RPM) better in compared to the one without momentum injection. Similarly, the high recovery led to a tremendously lower of 51% (500 RPM) and 99% (1000 RPM), respectively. In sum, these findings generated a stall angle delay of up to 26% (500 RPM) and 78% (1000 RPM) accordingly.